Interpreting osteoarthritis in bioarchaeology: Highlighting the importance of a clinical approach through case studies from prehistoric Thailand. (February 2017) - Domett, Kate; Evans, Caitlin; Chang, Nigel; Tayles, Nancy; Newton, Jennifer
Abstract: Osteoarthritis has a multifactorial aetiology. Despite this, and the incomplete understanding of the exact pathogenesis of osteoarthritis, many bioarchaeologists continue to attempt to link the prevalence of osteoarthritis with past behaviour and activity. This study aims to investigate the true impact of osteoarthritis on the people of prehistoric Ban Non Wat, northeast Thailand (1750 BCE to 500 CE). Through the analysis of the prevalence of osteoarthritis in each major joint and some individual case studies, the impact of this disease is detailed with reference to their social and physical environment. Two hundred and twenty nine adult individuals (45 Neolithic, 141 Bronze Age and 43 Iron Age) from Ban Non Wat with one or more major joint observeable were assessed for the presence and extent of osteophyte development, subchondral porosity and eburnation. The results showed no significant differences in prevalence across time or sex across the 2250 years represented by these skeletons. Although not significant, osteoarthritis was consistently high in elbows and knees across the Neolithic and Bronze Age phases, with the Iron Age not providing robust data. Four individuals with the most severe polyarticular osteoarthritis are detailed, indicating the varied nature of the disease and its potentially disabling effects on quality of life. This study reviews the most up to date clinical science to highlight that the study of osteoarthritis in past populations can be used to investigate disability and quality of life. Highlights: Osteoarthritis prevalence calculated for Ban Non Wat, prehistoric Thailand No significant difference in osteoarthritis over time or between sex The importance of clinical literature in bioarchaeology Osteoarthritis, as single factor, cannot be linked to detailed accounts of physical activity in past populations The impact of osteoarthritis on disability and quality of life in prehistory is often overlooked